5 Why Analysis Implementation To Detect Root Cause Of Rejected Product (Study At Aerospace Industry) - et. al., Arief Rahmana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose this paper is to detect the root cause of rejected product at aerospace industry. The rejected product is a minor defect that find in machining process. We found 1.47% of rejected product and it is higher than acceptable level. 5 why analysis was used to detect the root cause of rejected product in order to provide effective solution for this problem. There are four type of problem that focused in this research i.e. Total Damage, Incorrect, Mismatch, and Undercut. Based on 5 why analysis we found the root cause of total damage is there was not standard adjustment of speed between new machine and real system and we propose corrective action is making standardization for adjustment of speed between new machine and real system, the root cause of incorrect is there was no discipline in doing job and we propose corrective action is training and supervision for programmer, the root cause of mismatch is there was no appropriate strategy to make clamping system in tolerance and we propose corrective action is training about strategic strategy, and last the root cause of undercut is there were not coordination and standardization and we propose corrective action is carrying out coordination between unit and make configuration standard.